2019
DOI: 10.1177/0144598719832712
|View full text |Cite
|
Sign up to set email alerts
|

Concepts and characteristics of a U-shaped docking well geothermal heat extraction system

Abstract: Environmental pollution in China is getting worse. The effective use of geothermal energy can solve the problem of greenhouse gas emissions. This paper introduces a new type of medium-deep geothermal energy utilization system named U-shaped docking well geothermal heat extraction system and analyzes its characteristics. The results show that the system can meet the needs of daily heating, and the heat transfer effect of this system is greater than the concentric casing heat exchange systems. This study provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…UCLGS refers to a U‐shaped well formed by steel casing in both vertical and horizontal engineering wells. When working, the fluid working fluid completes the heat transfer via the descending, horizontal, and ascending sections and then enters the ground heat exchanger to complete the closed cycle 11 . Sun et al 12 developed a model for simulating CO 2 flow in the UCLGS and proposed two new concepts of critical position and effective distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCLGS refers to a U‐shaped well formed by steel casing in both vertical and horizontal engineering wells. When working, the fluid working fluid completes the heat transfer via the descending, horizontal, and ascending sections and then enters the ground heat exchanger to complete the closed cycle 11 . Sun et al 12 developed a model for simulating CO 2 flow in the UCLGS and proposed two new concepts of critical position and effective distance.…”
Section: Introductionmentioning
confidence: 99%
“…When working, the fluid working fluid completes the heat transfer via the descending, horizontal, and ascending sections and then enters the ground heat exchanger to complete the closed cycle. 11 Sun et al 12 developed a model for simulating CO 2 flow in the UCLGS and proposed two new concepts of critical position and effective distance. Furthermore, Song et al 13 reported an unsteady heat transfer model for UCLGS, which took in account with the change of convective heat transfer coefficient and analyzed influences of important parameters on UCLGS performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, closed-loop geothermal systems based on geothermal water recharge technology that consist of injection, horizontal, and production wells have been proposed (Fallah et al, 2021;Li, et al, 2019a;Sun et al, 2018). These systems are efficient and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…However, several current studies on U-shaped geothermal wells focus on their concept and nature (Li, et al, 2019a). Existing studies have developed mathematical models for flow and heat transfer to determine the relation between the well structure, wellbore size, process parameters, and working fluid physical parameters and the heating power and outlet temperature (Li, et al, 2019a;Liao et al, 2021;Lyu et al, 2020;Sun et al, 2019). The finding of such studies have laid the foundation for developing geothermal energy technology using U-shaped geothermal wells.…”
Section: Introductionmentioning
confidence: 99%